Avaliação do processo de implantação do Projeto Político Pedagógico nas Escolas da Rede Estadual de Ensino: um estudo de caso em Quixadá-CE - Costa, Adriana Gonçalves de Sales (2019)
In this dissertation, we approach the elaboration of the Political-Pedagogical Project (PPP) as an alternative of democratic management in the public school, in times of politics that do not share these values of the democratic management. In the various decision-making actions taken through democratic school management, there is the elaboration and execution of the PPP, which should point out a direction, direction, and explicit meaning to be established by the public school. We investigate how the process of elaboration of this management policy is carried out, in a school in the city of Quixadá/Ce, considering the Brazilian educational context, considering the world economic scenario of the last decades and its connection with the investigated school reality. The methodology used was based on the quantitative and qualitative research, and the case study focused on the emphasis on the perspective of critical-dialectical evaluation, in depth, in the axes of the social and institutional context, as paradigms of public policy evaluation. Especially educational ones. The instruments of the qualitative research were the structured questionnaire and the interview with the focus group, articulated with the available theoretical framework on the subject. In this discussion, we dialogue with Ilma Passos Alencastro Veiga, our main theoretical reference. The results found in the investigation show that the PPP is in line with the school reality, but in order to be effectively elaborated and / or executed, it needs the participation of the entire educational community, and to function as an agreement between the various actors, in order to contribute to the positive repercussion in the school context. In the final considerations, we affirm that it is necessary to materialize the PPP through collective actions in a document that directs and organizes the pedagogical work of the school, strengthens its autonomy and the participation of the educational community, executing and evaluating its own work, being responsible for the future of the institution.